Golden SusPtrit: a genetically well transformable barley line for studies on the resistance to rust fungi - Yeo, Freddy Kuok San; Hensel, G.; Vozabova, T.; Martin‑Sanz, A.; Marcel, T.C.; Kumlehn, J.; Niks, Rients E. (Springer Berlin Heidelberg, 2013)
Nonhost and partial resistance to Puccinia rust fungi in barley are polygenically inherited. These types of resistance are principally prehaustorial, show high diversity between accessions of the plant species and are genetically associated. To study nonhost and partial resistance, as well as their association, candidate gene(s) for resistance must be cloned and tested in susceptible material where SusPtrit would be the line of choice. Unfortunately, SusPtrit is not amenable to Agrobacterium-mediated transformation.